Development of taekwondo physical instruments: Test ages of 14-17 years old - Sringgih, H.; Tandiyo, R.; Soegiyanto (Journal of Physical Education and Sport, 2018)
The purpose of this study was to develop a physical test model of taekwondo athlete category (kyorugie) age 14-17 years. This type of research is R and D research (Research and Development). The research was conducted in several places, namely: Purwokerto, Yogyakarta, Sukoharjo and Surakarta in 2017, a sample of 300 athletes consisting of 150 male athletes and 150 athletes of the castle. Confirmatory factor analysis technique through SPSS program 23.00 with the provision if the measure of sampling adequacy (MSA> 0.5) then the instrument is feasible to use and (MSA <0.5) then the instrument is not feasible to use with significant level á = 0.05, for confirmed the latent variables that determine the physical quality of taekwondo athletes in the category of matches (kyorugie) ages 14-17. In this development study, the steps to be taken include: (1) preliminary study (literature study and field study), (2) planning (conducting analysis), (3) initial draft design, (4) draft validation (5) small group trial and revision, (6) large group trial and revision, (7) final result. Validity uses content validity, reliability using Retrone's Alpha test retest and T_skor to equalize units. The result of this research are 10 physical test indicator ata taekwondo athlete category (kyorugie) age 14 - 17 year old son and daughter consist of reliability test obtained result (1) sit and reach test 0,719 and 0,609; (2) The reaction rate test (ruller drop test) of 0.674 and 0.540; (3) Coordination test (eye, hand and foot coordination) of 0.809 and 0.712; (4) The stroke balance test of 0.640 and 0.731; (5) Triple-jump test of 0.801 and 0.749; (6) Hex test (hexagon obstacle test) of 0.608 and 0.608; (7) The maximum velocity test (30m hurdles) of 0.817 and 0.740; (8) Hand Grip strength of 0.771 and 0.737; (9) Muscle endurance test (push up) of 0.871 and 0.737; and (10) Cardiorespiratory endurance test (multi-stage run) of 0.799 and 0.814. The resulting product is a guidebook, test model and norm of physical test t taekwondo category of match (kyorugie) age 14-17 years.